Successful using of combined interscalene block and deep cervical plexus block for clavicle fracture in patients with impaired airway integrity due to combat injury - Ergun Mendes; Aziz Yarbil; Ali Bestami Kepekci; Oya Yalcin Cok (National Scientific Medical Center, 2021)
General anaesthesia has a priority in surgical interventions of clavicle; however, regional techniques may come to the fore in the presence of increased risk factors. The innervation of the clavicle region is very complex and has not been fully described; therefore, only a limited number of different regional anaesthesia approaches should be considered. Here, we present the management of a clavicle fracture with a combination of an interscalene block (ISB) and deep cervical plexus block (dCPB) in a patient with severe maxillo-facial trauma (MFT) and diaphragmatic hernia due to combat injury. A 35-year-old male admitted to the emergency room as a war-wounded patient had suffered MFT and an unstable clavicle defect during the Syrian War. A diaphragmatic hernia was also detected during examination. The patient underwent operation with regional anaesthesia of the clavicle under spontaneous respiration. With standard monitoring and sedation, ISB and dCPB were performed under ultrasound guidance with a mixture of 0.25% bupivacaine (20 mL) and 0.5% lidocaine (10 mL). In the perioperative period, the patient's vital signs remained stable. The patient had no pain during the surgery. We suggest that the combination of ISB and dCPB is an efficient option for management of clavicle fracture in patients with multiple comorbidities.